Islamophobia Values in The French Magazine Charlie Hebdo's Cartoons: A Semiotic Perspective of Roman Jakobson - Aldrian, Aldrian; Lestari, Septi; M. Anwar Mas'adi (JURNAL PENELITIAN KEISLAMAN, 2024)
This study analyzes two cartoons from Charlie Hebdo, employing six elements of Roman Jakobson's semiotics. It's a descriptive qualitative study using cartoon. The results of the study show that: 1) the cartoon edition 1011 consists of one addresser, Jean Cabut; two addressees, Prophet Muhammad SAW and Islam; one contact, Charlie Hebdo magazine; two contexts, social and religious-social; three codes with their respective messages, it can be concluded with the caricaturist's satire towards the whipping law found in Islamic Sharia; 2) the cartoon with the subtitle "L'amour, plus fort que la haine" consists of one addresser, Renald Luzier; one addressee, Muslim extremist groups; one contact, Charlie Hebdo magazine as one of the mass media in France; two contexts, social and religious-social; two codes with their respective messages, which can be concluded with the peace signal that the cartoonist wants to convey after the burning incident of the Charlie Hebdo magazine office.